A pharmacokinetic/pharmacodynamic model for AMG 416, a novel calcimimetic peptide, following a single intravenous dose in healthy subjects. (2nd May 2014) - Shen, Jun; Xiao, Jim; Pickthorn, Karen; Huang, Saling; Bell, Gregory; Vick, Andrew; Chen, Ping
Abstract AMG 416 is a novel peptide agonist of the calcium‐sensing receptor. In support of the clinical development program, a pharmacokinetic (PK)/pharmacodynamic (PD) model was developed to describe the relationship between plasma AMG 416 levels and serum intact parathyroid hormone (iPTH) concentrations in healthy male subjects. AMG 416 plasma concentrations were characterized by a three‐compartment linear PK model, while serum iPTH levels were described by an indirect response model with drug effect on the production of iPTH characterized with an inhibitory Emax model. The production of iPTH was modeled by a circadian rhythm function. The systemic clearance of plasma AMG 416 was estimated to be 6.94 L/h. Two sine functions best described iPTH circadian rhythm with an amplitude estimated to be 0.15 and 0.08, respectively. The maximum response Emax and the potency parameter EC50 were estimated to be 0.69 and 21.0 ng/mL, respectively. This work improved our understanding of the interaction between AMG 416 PK and iPTH concentrations in healthy adult male subjects. Data suggest additional PK/PD studies with AMG 416 are warranted in the hemodialysis population.